Legal Responsibility of Hospitals for Doctors' Misdiagnosis of Patient's Disease Based on Law No. 17 of 2023 concerning Health - Feni Rose Purba; Roida Nababan; Besty Habeahan (Journal of Legal and Cultural Analytics, 2025)
A doctor's misdiagnosis can cause harm to the patient. Hospitals as health service institutions have legal responsibility for doctors' misdiagnoses. This study aims to analyze the legal responsibility of hospitals for doctors' misdiagnoses of patient illnesses based on Law no. 17 of 2023, analyzes patients' legal efforts against misdiagnosis from a juridical and practical perspective. The research results show that patients can take legal action through administrative, civil and criminal channels. And research shows that hospitals have legal responsibilities for doctors' misdiagnoses, including compensation and restoring the patient's health. Article 193 of Law Number 17 of 2023 concerning health provides a strong legal basis for enforcing hospitals' legal responsibility for doctors' misdiagnoses.